Floating potential of dielectric target in plasma-beam discharge with magnet field - Dobrovol`s`kii, A.M.; Evsyukov, A.N.; Goncharov, A.A.; Protsenko, I.M. (Вопросы атомной науки и техники, 2006)
We present the results of investigations of the floating potential compensation of dielectric target in selfsustained plasma beam discharge in the magnetic field. We use gridless single-stage plasma accelerators with closed electron drift and narrow acceleration zone without of additional electron emitter as plasma beam source. When the source of such type works in collimated beam mode, lack of electrons in the ion flow leads to occurrence of positive charge on the target and reduces the efficiency of ion treatment. Existence of additional glow discharge in beam drift space can influence on target potential. We discuss experimental results of measurement of dielectric target potential for different conditions and proposal to solve the problem. Мы представляем результаты исследований компенсации плавающего потенциала диэлектрической мишени в самосогласованном пучково-плазменном разряде в магнитном поле. Мы используем бессеточный одноступенчатый плазменный ускоритель с замкнутым дрейфом электронов и узкой зоной ускорения без дополнительного эмиттера электронов в качестве источника пучка плазмы. Когда источник такого типа работает в режиме коллимированного пучка, недостаток электронов в ионном потоке ведет к возникновению положительного заряда на мишени и уменьшает эффективность ионной обработки. Существование дополнительного тлеющего разряда в пространстве дрейфа пучка может влиять на потенциал мишени. Мы обсуждаем экспериментальные результаты измерения потенциала диэлектрической мишени для различных условий и предлагаем решение проблемы. Ми представляємо результати досліджень компенсації плаваючого потенціалу діелектричної мішені у самоузгодженому пучково-плазмовому розряді у магнітному полі. Ми використовуємо безсітковий одно ступеневий плазмовий прискорювач з замкнутим дрейфом електронів та вузькою зоною прискорення без додаткового емітера електронів як джерело пучка плазми. Коли джерело такого типу працює в режимі колимованого пучка, недолік електронів у іонному потоці веде до виникнення позитивного заряду на мішені та зменшує ефективність іонної обробки. Існування додаткового жевріючого розряду у просторі дрейфу пучка може впливати на потенціал мішені. Ми обговорюємо експериментальні результати вимірювань потенціалу діелектричної мішені для різних умов та пропонуємо розв’язок проблеми.